2019
DOI: 10.4236/ce.2019.1013267
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms, Anxiety, Self-Esteem and Educational Social Skills in Public School Teachers

Abstract: Depression and anxiety symptoms are increasingly common in the world population and may damage different aspects of life. In the school context, these symptoms may affect teachers' self-esteem and educational social skills. This study aimed to evaluate and compare depression and anxiety symptoms, self-esteem and educational social skills in first and last grades elementary public school teachers, with 196 teachers, men and women, aged 18 years or older. The instruments applied were: a sociodemographic question… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
1
3
0
1
Order By: Relevance
“…The mean depression score was 21.9 (SD = 12.2). Compared to previous research, this score is similar to the mean score for a sample of teachers in an intervention study at baseline (Ebert et al: ‾X = 22.76, SD = 9.24, t = −1.23, P = ns), 37 but significantly higher than those of other studies 51 , 52 prior to the COVID-19 pandemic, for example Shen et al: ‾X = 18.48, SD = 9.4, t = 5.37, P < .001; Simor et al: ‾X = 15.45, SD = 9.56, t = 10.04, P < 001). The mean score in the current study is also significantly higher than that reported for a sample of teachers during COVID-19 53 : Truzoli et al: ‾‾X = 16.3, SD = 9.5, t = 8.73, P < 001).…”
Section: Resultssupporting
confidence: 81%
“…The mean depression score was 21.9 (SD = 12.2). Compared to previous research, this score is similar to the mean score for a sample of teachers in an intervention study at baseline (Ebert et al: ‾X = 22.76, SD = 9.24, t = −1.23, P = ns), 37 but significantly higher than those of other studies 51 , 52 prior to the COVID-19 pandemic, for example Shen et al: ‾X = 18.48, SD = 9.4, t = 5.37, P < .001; Simor et al: ‾X = 15.45, SD = 9.56, t = 10.04, P < 001). The mean score in the current study is also significantly higher than that reported for a sample of teachers during COVID-19 53 : Truzoli et al: ‾‾X = 16.3, SD = 9.5, t = 8.73, P < 001).…”
Section: Resultssupporting
confidence: 81%
“…The prevalence in the sample of this study corresponds to the prevalence in the general population. On the other hand, the self-esteem score was significantly higher in Group B and slightly above that found in the general population (Hutz & Zanon, 2011;Hutz, Zanon, & Vazquez, 2014). This outcome may be explained considering the possible good working conditions in the studied sample, favoring low anxiety scores.…”
Section: Lis-d Lis-mentioning
confidence: 55%
“…The self-esteem assessment by the RSES indicated a general mean slightly higher than the mean of the general population, which is 32.9 points (Hutz, Zanon, & Vazquez, 2014). The highest self-esteem score was found in Group B, presenting a statistically significant difference (p = 0.04).…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…Um estudo com 196 professores de ensino fundamental de escolas públicas do interior do estado do Rio Grande do Sul, teve por objetivo avaliar e comparar sintomas de depressão e ansiedade, autoestima e habilidades sociais educativas. Foram encontradas correlações moderadas e negativas entre sintomas de depressão, ansiedade e autoestima, e uma correlação fraca e positiva entre autoestima e habilidades sociais educativas (Medeiro et al, 2019).…”
Section: Introductionunclassified